Antitumor Effects of Esculetin, a Natural Coumarin Derivative, against Canine Mammary Gland Tumor Cells by Inducing Cell Cycle Arrest and Apoptosis - Jawun Choi; Min-Jae Yoo; Sang-Youel Park; Jae-Won Seol (Veterinary Sciences, 2023)
Mammary gland tumors are the most common neoplasms in female dogs, of which 50% are malignant. Esculetin, a coumarin derivative, reportedly induces death in different types of cancer cells. In this study, we explore the anticancer effects of esculetin against CMT-U27 and CF41.mg canine mammary gland tumor cells. Esculetin significantly inhibited the viability and migration of both CMT-U27 and CF41.mg cells in a dose- and time-dependent manner. Flow cytometric analysis and terminal deoxynucleotidyl transferase dUTP nick-end labeling assay revealed increased numbers of annexin-V-positive cells and DNA fragmentation. Furthermore, a cell cycle analysis demonstrated that esculetin blocked the cell progression at the G0/G1 phase and the S phase in CMT-U27 and CF41.mg cells. These results were supported by a Western blot analysis, which revealed upregulated protein expression of cleaved caspase-3, a marker of apoptosis, and downregulated cyclin-dependent kinase 4 and cyclin D1 protein, the cell cycle regulators. In conclusion, this novel study proves that esculetin exerts in vitro antitumor effects by inducing apoptosis and cell cycle arrest in canine mammary gland tumors.